Inovasi Kebijakan Literasi Baca Tulis di Madrasah Berbasis Pesantren (Studi Kasus di MA Nurul Huda Mangunsari Tekung) - Farikhah, Mir'atul; Nurhidayati, Titin (MANAGIERE: Journal of Islamic Educational Management, 2025)
Reading and writing literacy is a crucial skill in pesantren-based madrasahs, but it faces challenges such as limited reading materials, conventional methods, and minimal technology use. This qualitative case study was conducted at MA Nurul Huda Mangunsari. Data were collected through in-depth interviews, literacy activity observations, and policy document analysis. The school integrates kitab kuning literacy with general reading, implements mandatory book reviews, and utilizes student blogs for digital literacy. Key enablers include pesantren culture, leadership support, and community involvement, while limited resources and teacher training are major obstacles. These literacy innovations effectively enhance students’ critical reading, writing skills, and reading interest. The model is replicable for similar institutions. Future studies should explore the impact of digital literacy on students’ critical thinking abilities.